UPAYA PENCEGAHAN PENULARAN COVID-19 DI KELURAHAN PUHUN PINTU KABUN KOTA BUKITTINGGI - Arinil Haq; Yeffi Masnarivan; Detri Mayang Sari; Hukma Shabiyya; Muhammad Fadhil (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Covid-19 cases began to be reported in Indonesia with two positive confirmed cases on March 2, 2020. As of May 2, 2020, in West Sumatra Province, 182 confirmed cases of Covid-19 had been found. Current problems in society related to Covid-19 include the high urgency to prevent the transmission of Covid-19, especially at the individual or community level, such as wearing masks, maintaining hand hygiene, consuming foods with balanced nutrition, and others. This community service aims to improve community food security by distributing necessities and increasing public knowledge through leaflet media and non-medical masks. Community service was carried out at RW 003, Puhun Pintu Kabun, Bukittinggi City. The target participant is middle to lower economic status or is economically affected by the Covid-19 pandemic. Some community service participants filled out a questionnaire to assess the level of knowledge related to Covid-19 in general. The activities of distributing necessities, leaflets, and masks have been carried out well for 40 target participants. Based on the results obtained from the public knowledge overview questionnaire, it is known that most of the knowledge is good. Right knowledge is expected to be followed by attitudes and behaviors in efforts to prevent Covid-19. It is recommended that the available implement efforts to prevent the transmission of Covid-19 that have been conveyed through leaflet media, including using masks, maintaining hand hygiene, and others.